Implementation of Information Technology and Traceability for Rice Supply Chain - Bunvorn, Pichcha; Sopadang, Apichat; Jomjunyong, Sermkiat (Thai Industrial Engineering Network Journal, 2018)
Nowadays, information technology plays an important role in enhancing the efficiency and advantages in the commercial business. This study brings back information and retrieval systems. To make it easier for entrepreneurs (farmers) to reach consumers. Through ecommerce with the development of a website for farmers and consumers to share. Consumers will be able to check the return of goods. To ensure the purchase. And farmers use the information obtained from the order to develop and improve the quality of products. To increase the value of logistics and supply chain. Creating a data network for entrepreneurs (farmers) in Chiang Mai, Chiang Rai and Lampang participated in the study. And from tracking sales statistics and user surveys. After 3 months, the value of rice can be increased by 25 percent and the sales by 20 percent. The system also provides useful information to operators. To be able to develop and adapt to the changing market in the future.